Peningkatan Wawasan Penerapan Model Pembelajaran Berorientasi HOTS (Higher Order Thinking Skill) Bagi Guru MTs dan MA - Nur Aini Puspitasari; Syarif Hidayatullah (University of Islam Malang, 2020)
This training aims to improve the ability of teachers to apply HOTS-oriented learning models. The method used in this activity is the method of lecture, discussion, and practice. The result of this activity is an increase in the number of teachers' understanding of HOTS-oriented learning models with a percentage of 88%. Learning activities undertaken have led to high-level thinking (HOTS) reaching a percentage of 83%. The lesson plans made have led to high-level thinking that reaches a percentage of 81%. The learning approach has used SCL which reached a percentage of 84%. Participants have applied HOTS-oriented learning model that includes discovery learning, problem based learning, and project based learning has reached 84%. It can be concluded that this activity has increased the insight of teachers about HOTS-based learning practices theoretically and practically.